The invention of capitalism : classical political economy and the secret history of primitive accumulation - Perelman, Michael (E-Duke books scholarly collection., 2000)
Rethinks the history of classical political economy by assessing the Marxian idea of "primitive accumulation," the process by which a propertyless working class is created.